PENGGUNAAN STRATEGI PEMBELAJARAN BERBASIS PEMECAHAN MASALAH UNTUK MENINGKATKAN KECAKAPAN MENYAMPAIKAN PENDAPAT SISWA SMPK WIGNYA MANDALA TUMPANG - Suarniati, Ni Wayan; Kristianingsih, G. Niken Sri; Suprastowo, Agus (Jurnal Likhitaprajna, 2019)
This study aims to describe the improvement of skills in expressing opinions of junior high school students through the use of PBL on PPKn subjects. Skills to express opinions are accuracy, choice of words (diction), fluency, relevance, clarity, performance and respect for others. The success of the action is indicated by 75% completeness criteria. The research design used is Classroom Action Research (CAR) which includes the stages of planning, implementation, observation and reflection. The method of data collection consists of observation sheets, interviews and documentation. Data analysis techniques use qualitative analysis techniques with percentages. The results of the analysis prove that PBL can improve the ability to express the opinions of junior high school students with an average value of very good and good criteria which is 78.23%, which means that PBL can improve the skills of expressing opinions of SMPK students through civic education subjects.Â Keywords: problem based learning, skills, student opinions